Widespread cis-regulatory convergence between the extinct Tasmanian tiger and gray wolf - Feigin, Charles Y.; Newton, Axel H.; Pask, Andrew J. (Genome Research, 2019)
The extinct marsupial Tasmanian tiger, or thylacine, and the eutherian gray wolf are among the most widely recognized examples of convergent evolution in mammals. Despite being distantly related, these large predators independently evolved extremely similar craniofacial morphologies, and evidence suggests that they filled similar ecological niches. Previous analyses revealed little evidence of adaptive convergence between their protein-coding genes. Thus, the genetic basis of their convergence is still unclear. Here, we identified candidate craniofacial cis-regulatory elements across vertebrates and compared their evolutionary rates in the thylacine and wolf, revealing abundant signatures of convergent positive selection. Craniofacial thylacine–wolf accelerated regions were enriched near genes involved in TGF beta (TGFB) and BMP signaling, both of which are key morphological signaling pathways with critical roles in establishing the identities and boundaries between craniofacial tissues. Similarly, enhancers of genes involved in craniofacial nerve development showed convergent selection and involvement in these pathways. Taken together, these results suggest that adaptation in cis-regulators of TGF beta and BMP signaling may provide a mechanism to explain the coevolution of developmentally and functionally integrated craniofacial structures in these species. We also found that despite major structural differences in marsupial and eutherian brains, accelerated regions in both species were common near genes with roles in brain development. Our findings support the hypothesis that, relative to protein-coding genes, positive selection on cis-regulatory elements is likely to be an essential driver of adaptive convergent evolution and may underpin thylacine–wolf phenotypic similarities.
10.1101/gr.244251.118